Alienation between philosophy and sociology: a theoretical study - Almazrouei, Jasem; Kaouache , Raouf (Al-Adab Journal, 2024)
This study seeks to describe the development stages of alienation from philosophy to sociology and shed the light on the transformations that has been occurred in the concept from different aspects. The study adopts a descriptive approach and dealt with three stages of the development of the idea of alienation, starting with the philosophical stage represented by the efforts of “Thomas Hobbes”, “John Locke”, “Jean-Jacques Rousseau”, and “Friedrich Schiller” which included the intellectual contributions explained alienation based on the legal and religious context. Followed by the Hegelian stage represented by “Friedrich Hegel “where alienation turned into a concept concerned with studying the core of human reality, and arrive to the scientific stage, which contained the contributions of sociologists in the fields of work, bureaucracy, and the social system. “Marx” looked to alienation as social-historical phenomenon linked to the social and economic conditions of capitalist society, while “Durkheim“ explained it by the absence of social standards. Also, “Fromm“ explained it as a loss of freedom which is a result of societal control and technological development. Finally, “Seeman “presented the concept basic and derived meanings of alienation, which led to extract five independent elements. Reaching the Islamic stage, contributions of Islamic thought regarding the concept of estrangement have been presented. Among these contributions are those of “Ibn al-Qayyim” who views estrangement as a path to reaching Allah, “Ibn Bajjah” who links estrangement to the virtuous city, and “Abu Hayyan” who depicts estrangement as isolation. These perspectives offer diverse and nuanced insights into the phenomenon of estrangement within Islamic philosophical discourse.أعلى النموذج       In general, the results revealed the transformation of alienation from a theoretical philosophical to a scientific and applied topic that can be studied and analysed from a social perspective through three stages, and a result of the intellectual contributions of many philosophers and scientists.